Addressing the problem of self-diagnosing of illnesses in Pakistan - Ehtesham, Sameer; Ahmad, Muzamil; Ahmad, Muizz (Journal of the Pakistan Medical Association, 2025)
Madam, the rise of misinformation and clear disparities in Pakistan’s healthcare system has led to a concerning surge in self-diagnosis and self-medication. While the internet has provided open access to information, it has also created a breeding ground for unverified health advice, leading individuals to make potentially harmful decisions about their well-being. This not only endangers individual health but also poses significant public health risks, such as worsening mental well-being, and the exacerbation of antibiotic resistance. Without proper medical insight, people turn to self-evaluation, often misjudging their conditions. A recent study indicates that approximately 75% of Pakistanis self-diagnose at least once in their lifetime (1), while another study shows 84.8% Pakistanis resort to self-medication, primarily relying on painkillers, antipyretics, and cough syrups (2). Self-diagnosing often leads to a range of issues, including increased patient anxiety, self-treatment, and illegal medication purchases. Misdiagnosing a disorder can mask an underlying condition, thereby delaying treatment, and worsening prognosis (3). This issue is exacerbated by online content targeting youth under the guise of promoting mental well-being, thereby often spreading misinformation and insecurities. Research shows only 21% of attention deficit hyperactivity disorder-related social media content is helpful (4). A study on Pakistani youth, aged 18-24 found that mental health content is often consumed when viewers are emotionally vulnerable and prefer visually engaging media such as reels, infographics, and memes (5). One of the most concerning consequences of self-diagnosis is the misuse of medications, particularly antibiotics. Many individuals, Influenced by online contentthat they have a bacterial infection, resort to taking antibiotics without a prescription. This practice contributes to the growing crisis of antibiotic resistance. The Widespread misuse of antibiotics, driven by self-diagnosis, accelerates this crisis, making it harder to treat common infections and increasing the emergence of multi-drug-resistant bacteria (6). It is crucial to address this issue early to minimize its societal harm. Affordable healthcare should be prioritized in both urban and rural areas. The public should be actively encouraged to seek professional medical advice for physical and mental illnesses must be reinforced. Health services should utilize social media to deliver accurate medical information through official pages, institutions, and government-operated TV channels, thereby countering any and all misinformation.